Community‐wide mesocarnivore response to partial ungulate migration. Issue 6 (29th September 2014) - Henden, John‐André; Stien, Audun; Bårdsen, Bård‐Jørgen; Yoccoz, Nigel G.; Ims, Rolf A.; Hayward, Matthew
Summary Mesocarnivores increase in number and geographic range in human‐disturbed ecosystems with cascading negative impact on biodiversity. To mitigate such impacts, it is essential to identify the proximate causes of such mesocarnivore releases. Here, we assess to what extent increased partial migration in semi‐domesticated tundra reindeer induce a response in boreal and arctic mesocarnivores. We used a large‐scale and multiyear quasi‐experimental study design with camera traps deployed on coastal tundra peninsulas in northern Norway to estimate area occupancy of the whole carnivore community. These peninsulas represent summer pastures for separate semi‐domestic reindeer herds that, owing to different degrees of partial migration, now display spatially and temporally variable densities of year‐round resident reindeer. We estimated resident reindeer density by means of aerial surveys. Area occupancy of all the recorded carnivore species increased strongly when resident reindeer densities exceeded 1·5 deer km−2. Most of the increasing carnivore species were typical boreal forest species, implying range expansions into tundra when provided with stable food resources (prey and carrion) in terms of resident reindeer. Synthesis and applications. We found that boreal mesocarnivores, known to negatively impact the productivity of reindeer and arctic wildlife of conservation concern, steeply increased in tundra areas with many year‐round resident reindeer due to increased partial migration. To avoid such negative impacts, actions should be taken to minimize residency in tundra reindeer.